PERAN AYAH DALAM MENDIDIK ANAK BERDASARKAN Al-QUR'AN (Tinjauan Tentang Cara Para Nabi-Nabi Dalam Mendidik Anak) - Rahmadianti Aulia (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2018)
The Father is a figure that contribute to development the way of thinking and morality of the children. Many scholars today believe that is the father not only struggle for economic of their family but also for a wide scope of activity included education of the children. Its very interesting to know that has been written in al-Quran long before the expert said. So, the aim of this study is to describe the fact in al-Quran related to the role of the father educated and the strategy they used in detail. This study applied descriptive qualitative research in which the data are obtained from some dialogis verses in Al-Quran. The data obtained by taking note technique, reading technique and supported by document analisys technique. After analyzing the data, it is found that the father was a person who knew deeply of their children character. Al-Quran teach the reader to be a wise father for their children, to understand their problem, not so emotional, speak the truth and avoid the trouble. Beside, the father must trust their children with all of sincere heart and soul.